Effects of the 2010 Affordable Care Act Dependent Care Provision on Military Participation among Young Adults - Pinka Chatterji; Xiangshi Liu; Baris K. Yörük (Center for Economic Studies and ifo Institute (CESifo), 2018)
In this study, we test whether the Affordable Care Act's (ACA) dependent care provision is associated with young adults' propensity to be in the armed forces and to have military health insurance. We use a difference-in-difference (DD) approach, comparing the outcomes of young adults targeted by the policy change (ages 23-25 years old) before and after the ACA was passed to those of a comparison group of slightly older young adults (ages 27-29 years old) who were not targeted. The findings indicate that the ACA dependent care provision is associated with statistically significant reduction in the likelihood that young adults have military health insurance. We also find that the ACA induced young adults to drop military health insurance even while they remained on active duty.
Keywords: I18; 330; affordable care act; ACA; dependent care; health insurance; military; armed forces